The Future is Now: Reducing Psychological Distance to Increase Public Engagement with Climate Change - Jones, Charlotte; Hine, Donald W.; Marks, Anthony D. G. (Risk analysis, 2017)
Many people perceive climate change as psychologically distant—a set of uncertain events that might occur far in the future, impacting distant places and affecting people dissimilar to themselves. In this study, we employed construal level theory to investigate whether a climate change communication intervention could increase public engagement by reducing the psychological distance of climate change. Australian residents (N = 333) were randomly assigned to one of two treatment conditions: one framed to increase psychological distance to climate change (distal frame), and the other framed to reduce psychological distance (proximal frame). Participants then completed measures of psychological distance of climate change impacts, climate change concern, and intentions to engage in mitigation behavior. Principal components analysis indicated that psychological distance to climate change was best conceptualized as a multidimensional construct consisting of four components: geographic, temporal, social, and uncertainty. Path analysis revealed the effect of the treatment frame on climate change concern and intentions was fully mediated by psychological distance dimensions related to uncertainty and social distance. Our results suggest that climate communications framed to reduce psychological distance represent a promising strategy for increasing public engagement with climate change.